PEREMPUAN ORANGTUA TUNGGAL DALAM INSTITUSI KELUARGA DI DESA KOTO TANDUN KECAMATAN TANDUN KABUPATEN ROKAN HULU - Iis Maharani Pratama Marpaung; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to find out single-parent women carry out their family functions and describe the involvement of other social institutions outside the nuclear family in carrying out family functions. Determination of informants using purposive sampling technique, namely being a single parent woman due to the death of her husband, having a minimum of three family dependents, working in the public sector, being a single parent woman for a maximum of six years. The results of the study are that the economic function that is carried out by single parent women is to fulfill the economic needs of the family by working. The thing that distinguishes the implementation of the family functions of the informants is in carrying out the protection function, affection function, religious function and socialization function in the family. While the involvement of educational institutions carries out the function of family socialization, namely being a vehicle for fostering, education, socialization for children and a place of protection for children, economic institutions carrying out family economic functions by looking at the role of markets and financial institutions, religious institutions carrying out family religious functions as a vehicle for good friendship. creating a sense of brotherhood and kinship, religious leaders who help provide advice and calm the hearts of single-parent women's families, and religious organizations that provide compensation assistance to orphans, political institutions carry out family protection functions to become service providers for single-parent women's families, protect families single-parent women through village officials, providing services in all administrative matters at the village office, as well as maintaining the ability of single-parent women's families to adjust to living conditions. changed.Keywords: single parent women, family function, social institutions